2000
DOI: 10.1128/aem.66.9.3891-3897.2000
|View full text |Cite
|
Sign up to set email alerts
|

Production and Consumption of Nitric Oxide by Three Methanotrophic Bacteria

Abstract: We studied nitrogen oxide production and consumption by methanotrophs Methylobacter luteus (group I), Methylosinus trichosporium OB3b (group II), and an isolate from a hardwood swamp soil, here identified by 16S ribosomal DNA sequencing as Methylobacter sp. strain T20 (group I). All could consume nitric oxide (nitrogen monoxide, NO), and produce small amounts of nitrous oxide (N 2 O). Only Methylobacter strain T20 produced large amounts of NO (>250 parts per million by volume [ppmv] in the headspace) at speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…For example, heterotrophic methane cycling bacteria closely related to Methylobacter comprised at least 16% of the detected sequences fifteen days after nitrate addition. Methylobacter species have been associated with denitrification under anaerobic conditions in previous studies (Ren et al, 2000) and also have been associated previously with marine anoxic zones (Lloyd et al, 2006). The increase in the relative abundance of methane cycling bacteria in the four month aged sample is perhaps unsurprising given that significant quantities of methane were detected in microcosm headspace, and that the electron equivalent calculations estimated that up to 90% of the added electron donor may have been consumed by methanogenesis.…”
Section: Molecular Ecology Of Nitrate Induced Biogenic U(iv) Reoxidationmentioning
confidence: 85%
“…For example, heterotrophic methane cycling bacteria closely related to Methylobacter comprised at least 16% of the detected sequences fifteen days after nitrate addition. Methylobacter species have been associated with denitrification under anaerobic conditions in previous studies (Ren et al, 2000) and also have been associated previously with marine anoxic zones (Lloyd et al, 2006). The increase in the relative abundance of methane cycling bacteria in the four month aged sample is perhaps unsurprising given that significant quantities of methane were detected in microcosm headspace, and that the electron equivalent calculations estimated that up to 90% of the added electron donor may have been consumed by methanogenesis.…”
Section: Molecular Ecology Of Nitrate Induced Biogenic U(iv) Reoxidationmentioning
confidence: 85%
“…NO production from nitrite, measured by the nitrosation of 2,3-diaminonaphthalene (DAN) (6) was proposed to involve enzymatic reduction of nitrite to NO followed by oxygen-dependent DAN nitrosation. NO production has also been shown in Serratia marcescens (7), Bacillus cereus (8), three species of methanotrophic bacteria (9), and the green micro alga Scenedesmus obliquus (10). Ji and Hollocher (11) concluded that nitrite-dependent NO production by E. coli was due to the activity of the membrane-associated (dissimilatory) nitrate reductase.…”
mentioning
confidence: 99%
“…Another possibility may be the presence of an active/functional nitrous oxide reductase produced from the plasmid-borne nos operon, thereby resulting in the rapid conversion of N 2 O to N 2 . To examine the second possibility, we checked N 2 O production after blocking the nos activity with purified acetylene [93], [94], [95]. As acetylene is also a potent inhibitor of methane monooxygenase [90], we performed this experiment either by adding methanol or without a carbon source.…”
Section: Resultsmentioning
confidence: 99%
“…The acetylene inhibition method [93], [94], [95] was used to verify the production of N 2 O by strain SC2. Briefly, NMS-grown log-phase cells (3.4 mg dry weight) were resuspended in 5 ml of fresh NMS medium supplemented with methanol (0.1% [vol/vol]) or without a carbon source in 25-ml serum bottles that were capped with butyl rubber stoppers.…”
Section: Methodsmentioning
confidence: 99%